Oracle SQL Developer 2.1 - Harper, Sue (Packt Publishing, 2011)
Covering SQL Developer fundamentals as well more intermediate and advanced topics, this book uses in-depth explanation and detailed examples to help you get the most out of Oracle SQL Developer. The book has a modular structure, so that you can dip into any chapter that covers your current area of focus and get going. This book is for Oracle developers who want to ease their database development, and enhance their productivity using Oracle SQL Developer. You should have a programming knowledge of SQL and PL/SQL, and a general familiarity with Oracle database concepts.